Peṇ vācan̲ai - Caṇmukacuntaram, Cuṭalaimuttu (Kāvyā, 2020)
Study on feminism and the voice of women in Tamil literature and folklore.
Literaturverzeichnis: Seite 263-264
Keywords: Tamil literature; History and criticism.; Feminism in literature.; Folklore; India; Tamil Nadu.; Tamil Nadu (India); Religious life and customs.